Current Understanding of the Earliest Human Occupations in the Americas: Evaluation of Becerra-Valdivia and Higham (2020). (2nd January 2022) - Potter, Ben A.; Chatters, James C.; Prentiss, Anna Marie; Fiedel, Stuart J.; Haynes, Gary; Kelly, Robert L.; Kilby, J. David; Lanoë, François; Holland-Lulewicz, Jacob; Miller, D. Shane; Morrow, Juliet E.; Perri, Angela R.; et al.
ABSTRACT: Various chronologies of the earliest Native American occupations have been proposed with varying levels of empirical support and conceptual rigor, yet none is widely accepted. A recent survey of pre-Clovis dated sites (Becerra-Valdivia and Higham 2020) concludes a pre-Last Glacial Maximum (>26, 500–19, 000 cal yr BP) entry of humans in the Americas, in part based on recent work at Chiquihuite Cave, Mexico. We evaluate the evidence used to develop this inference. To provide clarity, we present three explicit dispersal models for the earliest human dispersals to the Americas: Strict Clovis-First (13, 050 cal yr BP), Paleoindian (<16, 000 cal yr BP), and Pre-Paleoindian (>16, 000 cal yr BP, encompassing pre-LGM, preferred by Becerra-Valdivia and Higham (2020)), and we summarize the current genetic and archaeological evidence bearing on each. We regard all purported Pre-Paleoindian sites as equivocal and the Strict Clovis-First model to be equally unsupported at present. We conclude that current data strongly support the Paleoindian Dispersal model, with Native American ancestors expanding into the Americas sometime after 16, 000 cal yr BP (and perhaps after 14, 800 cal yr BP), consistent with well-dated archaeological sites and with genetic data throughout the western hemisphere. Models of the Americas' peopling that incorporate Chiquihuite or other claimed Pre-Paleoindian sites remain unsubstantiated.